Star Wars, the force awakens : the visual dictionary - Hidalgo, Pablo; Goodson, John; Lucasfilm, Ltd. (New York, New York : DK/Penguin Random House, 2015)
"... reveals all of the characters, creatures, droids, locations, and technology"--Page [4] of cover.
Peace Interrupted -- BB-8 -- Poe Dameron -- Lor San Tekka -- Stormtroopers -- Flametroopers -- FN-2187 -- Finn -- Kylo Ren -- Kylo Ren: Dark Warrior -- Captain Phasma -- Rey -- Rey: Survivor's Spirit -- Starship Graveyard -- Niima Outpost -- Unkar Plutt -- General Hux -- Finalizer Crew -- TIE Fighter Pilots -- Han Solo -- Chewbacca -- Rathtars -- Guavian Death Gang -- Kanjiklub -- General Organa -- Resistance Commanders -- Resistance Pilots -- Resistance Ground Crew -- C-3PO -- R2-D2 -- The Senate -- Starkiller Base -- Snowtroopers -- Maz Kanata -- Maz's Castle -- Castle Guests.
Companion to the motion picture Star Wars, episode VII, the force awakens.
Includes index.
"Disney/Lucasfilm"--Page [4] of cover.
Keywords: Force awakens (Motion picture) -- Juvenile literature; Force awakens (Motion picture); Star Wars films -- Miscellanea -- Juvenile literature; Star Wars films -- Miscellanea